Loss of Control Over Eating Scale (LOCES): Validation in undergraduate men and women with and without eating disorder symptoms. (December 2016) - Stefano, Emily C.; Wagner, Allison F.; Mond, Jonathan M.; Cicero, David C.; Latner, Janet D.
Abstract: The present study aimed to further validate the Loss of Control Over Eating Scale (LOCES) for use with undergraduate men and women with and without eating disorder (ED) symptoms. A total of 261 participants completed the LOCES and the Eating Disorder Examination – Questionnaire (EDE-Q) and were identified as non-clinical or having probable ED symptomatology based on previously used EDE-Q cutoff scores. Results indicated that the LOCES and its subscales were significantly associated with and a significant predictor of global ED pathology and binge episode frequency. The LOCES behavioral subscale appeared to be a stronger predictor of episode frequency compared to other subscales. The ED pathology groups reported significantly higher LOCES scores compared to the non-ED pathology groups. Binary logistic regression analyses revealed that the LOCES was able to accurately distinguish between those with ED pathology and those without ED pathology in the majority of cases. Findings from the present study suggest that the LOCES is highly predictive of ED pathology, strongly associated with ED cognitions and behaviors, and an accurate index for global eating disorder pathology. Future directions for research are discussed. Highlights: The LOCES is a predictor of global ED pathology and binge episode frequency. The LOCES behavioral subscale was a stronger predictor for ED pathology than other subscales. The LOCES accurately distinguished cases with and without ED pathology. Findings suggest the LOCES may be an accurate index for global ED pathology.